Transmission and display of sensor data from single board computer - Ang, Shandon Wei Shen (Nanyang Technological University, 2023)
Transmission and display of data have been widely explored by many over the years. However, the areas explored are mainly done in a closed environment and not been brought online. There are some disadvantages when it comes to doing it in a closed environment and the data and system cannot be monitored remotely. This means that maintenance or monitoring has to be done locally. This can cause time to be wasted as there is travelling time incurred. The purpose of this project is to research and develop a system which can record sensor data, transmit it online, to an online database or cloud, then display the data on a Graphical user interface (GUI) with the help of a single board computer. In future, development of the organization of a database system can be done to record more types of data and the development of the GUI for the ease of use for users. The most important features so far are to record sensor data and to transmit it online for storage before displaying, using a single board computer.